SARS-CoV-2 Dissemination Through Peripheral Nerves Explains Multiple Organ Injury - Fenrich, Matija; Mrdenovic, Stefan; Balog, Marta; Tomic, Svetlana; Zjalic, Milorad; Roncevic, Alen; Mandic, Dario; Debeljak, Zeljko; Heffer, Marija (Frontiers in Cellular Neuroscience, 2020)
Coronavirus disease (CoVID-19), caused by recently identified severe acute respiratory distress syndrome coronavirus 2 (SARS-CoV-2), is characterized by inconsistent clinical presentations. While many infected individuals remain asymptomatic or show mild respiratory symptoms, others develop severe pneumonia or even respiratory distress syndrome. SARS-CoV-2 is reported to be able to infect the lungs, the intestines, blood vessels, the bile ducts, the conjunctiva, macrophages, T lymphocytes, the heart, liver, kidneys, and brain. More than a third of cases displayed neurological involvement, and many severely ill patients developed multiple organ infection and injury. However, less than 1% of patients had a detectable level of SARS-CoV-2 in the blood, raising a question of how the virus spreads throughout the body. We propose that nerve terminals in the orofacial mucosa, eyes, and olfactory neuroepithelium act as entry points for the brain invasion, allowing SARS-CoV-2 to infect the brainstem. By exploiting the subcellular membrane compartments of infected cells, a feature common to all coronaviruses, SARS-CoV-2 is capable to disseminate from the brain to periphery via vesicular axonal transport and passive diffusion through axonal endoplasmic reticula, causing multiple organ injury independently of an underlying respiratory infection. The proposed model clarifies a wide range of clinically observed phenomena in CoVID-19 patients, such as neurological symptoms unassociated with lung pathology, protracted presence of the virus in samples obtained from recovered patients, exaggerated immune response, and multiple organ failure in severe cases with variable course and dynamics of the disease. We believe that this model can provide novel insights into CoVID-19 and its long-term sequelae, and establish a framework for further research.